The rate of formation and stability of abasic site interstrand crosslinks in the DNA duplex - Huskova, Andrea; Landova, Barbora; Boura, Evzen; Silhan, Jan (DNA repair, 2022)
DNA interstrand crosslinks (ICLs) strands pose an impenetrable barrier for DNA replication. Different ICLs are known to recruit distinct DNA repair pathways. NEIL3 glycosylase has been known to remove an abasic (Ap) site derived DNA crosslink (Ap-ICL). An Ap-ICL forms spontaneously from the Ap site with an adjacent adenine in the opposite strand. Lack of genetic models and a poor understanding of the fate of these lesions leads to many questions about the occurrence and the toxicity of Ap-ICL in cells. Here, we investigate the circumstances of Ap-ICL formation. With an array of different oligos, we have investigated the rates of formation, the yields, and the stability of Ap-ICL. Our findings point out how different bases in the vicinity of the Ap site change crosslink formation in vitro. We reveal that AT-rich rather than GC-rich regions in the surrounding Ap site lead to higher rates of Ap-ICL formation. Overall, our data reveal that Ap-ICL can be formed in virtually any DNA sequence context surrounding a hot spot of a 5'-Ap-dT pair, albeit with significantly different rates and yields. Based on Ap-ICL formation in vitro, we attempt to predict the number of Ap-ICLs in the cell.
Keywords: replikace DNA; Abasic site; poškození DNA; DNA damage; Cross-Linking Reagents; DNA Damage; DNA repair; DNA Repair; oprava DNA; reagencia zkříženě vázaná; DNA; Interstrand crosslink; Non-enzyme kinetics; DNA Replication